2018
DOI: 10.1186/s40645-017-0162-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep magnetic field stretching in numerical dynamos

Abstract: The process of magnetic field stretching transfers kinetic energy to magnetic energy and thereby maintains dynamos against ohmic dissipation. Stretching at depth may play an important role in shaping the field morphology and in the dynamo action. Here, we analyze snapshots from self-consistent 3D numerical dynamos to unravel the nature of field-flow interactions that induces stretching secular variation of the radial magnetic field at mid-depth of the shell. We search for roots of intense flux patches identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…Numerical dynamo models (Olson et al, 1999;Kageyama and Sato, 1997) have shown how columnar vortices twist the toroidal magnetic field lines to produce the poloidal field. Takahashi and Shimizu (2012) and Peña et al (2018) made a detailed analysis of terms in the magnetic induction equation. The present study looks at the dominant contributions to the axial dipole field and brings out the differences between kinematic and nonlinear dynamos in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical dynamo models (Olson et al, 1999;Kageyama and Sato, 1997) have shown how columnar vortices twist the toroidal magnetic field lines to produce the poloidal field. Takahashi and Shimizu (2012) and Peña et al (2018) made a detailed analysis of terms in the magnetic induction equation. The present study looks at the dominant contributions to the axial dipole field and brings out the differences between kinematic and nonlinear dynamos in this respect.…”
Section: Introductionmentioning
confidence: 99%